Recovering Civility during COVID-19 - Bonotti, Matteo; Zech, Steven T. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2021)
This Open Access book examines many of the challenges posed by the COVID-19 pandemic through the distinctive lens of civility. The idea of civility appears often in both public and academic debates, and a polarized political climate frequently leads to allegations of uncivil speech and behaviour. Norms of civility are always contested, even more so in moments of crisis such as a global pandemic. A focus on civility provides crucial insight and guidance on how to navigate the social and political challenges resulting from COVID-19. Furthermore, it offers a framework through which citizens and policymakers can better understand the causes and consequences of incivility, and devise ways to recover civility in our social and political lives. Matteo Bonotti is Senior Lecturer in Politics and International Relations at Monash University. Steven T. Zech is Lecturer (Assistant Professor) in Politics and International Relations at Monash University'.